2018
DOI: 10.1038/s41433-018-0144-x
|View full text |Cite
|
Sign up to set email alerts
|

A British Ophthalmological Surveillance Unit (BOSU) study into dysthyroid optic neuropathy in the United Kingdom

Abstract: This prospective British Ophthalmological Surveillance Unit (BOSU) study on dysthyroid optic neuropathy (DON) determines the incidence, presenting features and management throughout the UK. New cases were identified through the BOSU yellow card and an initial questionnaire and a subsequent 9-month follow-up questionnaire were posted out. From August 2015 to August 2016 DON was reported in 49 patients with 71 eyes affected, 22 patients had bilateral DON. The most common presenting symptom was blurred vision (83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 23 publications
1
29
0
2
Order By: Relevance
“… 8 Despite the widespread use of these modalities over decades for TED, the literature is mostly comprised of retrospective studies, Case reports and small case series which now guide practice patterns in the treatment of DON. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 There has only been one prospective, randomized controlled trial (RCT) to compare corticosteroids versus corticosteroids and surgical decompression for DON. 12 In this study, Wakelkamp et al reported similar initial outcomes after medical decompression and surgical decompression, and found that immediate surgical decompression did not result in better visual outcomes nor did it preclude the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Despite the widespread use of these modalities over decades for TED, the literature is mostly comprised of retrospective studies, Case reports and small case series which now guide practice patterns in the treatment of DON. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 There has only been one prospective, randomized controlled trial (RCT) to compare corticosteroids versus corticosteroids and surgical decompression for DON. 12 In this study, Wakelkamp et al reported similar initial outcomes after medical decompression and surgical decompression, and found that immediate surgical decompression did not result in better visual outcomes nor did it preclude the use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that MPT appears to be the first choice for active TAO with DON rather than immediate surgery, while a complete recovery can be achieved in the majority of patients with DON by combination therapy [15][16][17][18]. Numerous researches have investigated the clinical manifestations, diagnosis, and treatment of TAO so far, but researches on the benefits and timing of decompression surgery and MPTfor DON patients are deficient [17,[19][20][21]. is study investigated and compared the effect of combined treatment of orbital decompression and MPT on one eye of patients with bilateral DON, and the effect of separate MPT on the fellow eye of the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…TED with DON is mainly a result of crowding around the orbital apex with nerve compression secondary to expanded extraocular muscles [ 14 ] or some caused by optic nerve stretching without a crowded apex [ 15 ]. In a British study of 71 eyes of 49 patients with DON, most patients received initial corticosteroid therapy yet almost 50% required surgical orbital decompression [ 16 ]. A large American study of 163 eyes of 104 patients with DON received combined corticosteroid and orbital radiotherapy has reported that among the initially 95% successfully treated patients, ultimately 36.7% of them underwent elective surgery, including orbital decompression during the inactive phase of TED [ 17 ].…”
Section: Principle Of Don Treatmentmentioning
confidence: 99%